Challenges With Left Ventricular Functional Parameters: The Pediatric Heart Network Normal Echocardiogram Database - Minich, L. LuAnn; Altmann, Karen; Camarda, Joseph; Cohen, Meryl S.; Colan, Steven D.; Dragulescu, Andreea; Frommelt, Michele A.; Johnson, Tiffanie R.; Kovalchin, John P.; Lin, Lina; Mahgerefteh, Joseph; Nutting, Arni; et al. (Journal of the American Society of Echocardiography, 2019)
The reliability of left ventricular (LV) systolic functional indices calculated from blinded echocardiographic measurements of LV size has not been tested in a large cohort of healthy children. The objective of this study was to estimate interobserver variability in standard measurements of LV size and systolic function in children with normal cardiac anatomy and qualitatively normal function. The Pediatric Heart Network Normal Echocardiogram Database collected normal echocardiograms from healthy children ≤18 years old distributed equally by age, gender, and race. A core lab used two-dimensional echocardiograms to measure LV dimensions from which a separate data coordinating center calculated LV volumes and systolic functional indices. To evaluate interobserver variability, two independent expert pediatric echocardiographic observers remeasured LV dimensions on a subset of studies, while blinded to calculated volumes and functional indices. Of 3,215 subjects with measurable images, 552 (17%) had a calculated LV shortening fraction (SF) < 25% and/or LV ejection fraction (EF) < 50%; the subjects were significantly younger and smaller than those with normal values. When the core lab and independent observer measurements were compared, individual LV size parameter intraclass correlation coefficients were high (0.81-0.99), indicating high reproducibility. The intraclass correlation coefficients were lower for SF (0.24) and EF (0.56). Comparing reviewers, 40/56 (71%) of those with an abnormal SF and 36/104 (35%) of those with a normal SF based on core lab measurements were calculated as abnormal from at least one independent observer. In contrast, an abnormal EF was less commonly calculated from the independent observers’ repeat measures; only 9/47 (19%) of those with an abnormal EF and 8/113 (7%) of those with a normal EF based on core lab measurements were calculated as abnormal by at least one independent observer. Although blinded measurements of LV size show good reproducibility in healthy children, subsequently calculated LV functional indices reveal significant variability despite qualitatively normal systolic function. This suggests that, in clinical practice, abnormal SF/EF values may result in repeat measures of LV size to match the subjective assessment of function. Abnormal LV functional indices were more prevalent in younger, smaller children. •3215 normal echo studies were collected from healthy children ≤18 years of age.•17% had abnormal blinded core lab calculated values for LV SF <25% and/or EF <50%.•Those with abnormal SF/EF were significantly younger and smaller.•Repeat expert measurements of LV size showed good interobserver reproducibility.•Calculated LV functional indices, however, revealed significant variability.